Comparison among Modified Acid-Fast Stain and Some Immunological Methods in Diagnosis of Cryptosporidium parvum in Kut City - Rahi, Abdulsadah Abdulabbas (Journal of Wasit for Science and Medicine, 2022)
A total of 100 children who attending to Al-Karamah Teaching Hospital at Kut city were suffered from watery diarrhoea and abdominal pain were examined. The present study was conducted from October 2011 to January 2012. A thirty-four stool samples in which Cryptosporidium parvum oocysts had been seen by modified acid –fast stain examination were investigated, positivity detected with the ImmunoCard method, and Direct Fluorescent Antibody( DFA ) method was found to be (30%), (28%) and (34%) respectively. Children aged one month to 144 months presenting with acute or persistent diarrhoea were selected randomly. prevalence of Cryptosporidium parvum infection was significantly higher (59%) in children under one year old compared to children between (7-12) years old (4%). The infective rate of Cryptosporidium parvum in males was higher 17% than females 13% . Also, there was no significant difference among children in gender.